Eating out in five languages - Collin, S. M. H., 1966-; Guinard, Cécile; Jackson, Daisy; Laurendeau-Collin, Françoise (Bloomsbury, 2004)
This volume will help you decipher menus whether they are in English, French, German, Italian or Spanish. It has over 10,000 food and drink terms translated to and from English, covering dishes, ingredients, methods of cooking and useful phrases for ordering and asking for service.